Accretion processes in magnetic cataclysmic variables - a detailed study of UZ Fornacis - Khangale, Zwidofhelangani Ndamulelo (Department of Astronomy, 2022)
This thesis presents a multi-wavelength exploration of the emissions from magnetic cataclysmic variable (mCV) stars with specific focus on the eclipsing AM Her system, UZ Fornacis (hereafter UZ For). The main objective of this thesis is to investigate the underlying emission mechanisms as well as the accretion dynamics in this system with the intention of increasing our understanding of this class of objects as a whole. The presence of a strong magnetic field in UZ For makes it an interesting object in terms of how the magnetic field dominates the accretion dynamics and its influence on the emission processes. The eclipsing characteristics of this system, with a clearly defined ingress and egress of the main accretion spot, can be exploited to gain further insights through precise eclipse timings. The first part of this thesis presents 33 new mid-eclipse times spanning eight years of observations on UZ For. The new observations are used to test the two-planet model previously proposed to explain the periodic variations in the eclipse times of UZ For measured over the past ∼35 years. The results show that the proposed model does indeed follow the general trend of the new eclipse times. However, there are significant departures. In order to accommodate the new eclipse times, the two-planet model requires that one or both of the planets have highly eccentric orbits, i.e. e ≥ 0.4. Such multiple planet orbits are considered to be unstable. Whilst our new observations are consistent with two cyclic variations as previously predicted, significant residuals remain. This study explores the possibility that either additional cyclic terms, possibly associated with more planets, or other mechanisms, such as the Applegate mechanism are contributing to the eclipse time variations. The second part of this thesis presents phase-resolved spectroscopy of UZ For which allowed us to do a detailed Doppler tomography study of this target. The averaged blue spectrum is dominated by single- and/or double-peaked emission from HeII 4686 Å and the Balmer lines, as well as weak emission from HeI lines and the CIII/NIII blend at 4650Å. The averaged red spectrum shows strong emission from CaII lines at 8498 Å and 8542 Å and possibly weak emission from the NaI doublet at 8183 Å and 8194 Å. The strength of HeII 4686 Å line is comparable to that of Hβ line and this is typical for AM Her systems in a high state of accretion. The ratio of Hγ/Hβ ' 1 implying that these emission lines were formed in an optically thick region, that is, a region of high optical depth in the lines. Doppler tomography of the strongest features in the blue, HeII 4686Å and the Balmer lines (e.g. Hβ line), using both the standard and inside-out maps, revealed the presence of three emission regions: 1) the irradiated face of the secondary star, 2) the ballistic stream and the threading region, and 3) the magnetically confined accretion stream. The Doppler maps of emission lines in the red spectrum show the presence of emission from the irradiated face of the secondary star as well as emission from various parts of the ballistic and magnetically confined accretion stream. Also presented are the respective modulation Doppler maps of each line. These show that both the ballistic and magnetically confined accretion stream are modulated as well as the irradiated face of the secondary star. In addition to the above, the first simultaneous optical and MeerKAT radio observations of the eclipsing AM Her system UZ For are also presented. The optical data include SALT circular spectropolarimetry taken around the eclipse and SHOC and MeerLICHT photometry. The total intensity spectrum shows broad emission features with the continuum that rises in the blue. The percentage circularly polarized spectra show that UZ For is negatively polarized (up to ∼ −8%) in the blue and decreasing gradually towards the red. The circularly polarized spectrum shows the presence of three cyclotron emission features at ∼4500 Å, 6000 Å and 7700 Å, corresponding to harmonic numbers 4, 3 and 2, respectively. These features are dominant before the eclipse and disappears after the eclipse. The harmonics are consistent with the magnetic field strength of ∼57 MG seen at a viewing angle of 70◦ . To aid with the interpretation of the circular spectropolarimetry, simultaneous circular and linear photopolarimetric observations of UZ For obtained with the HIPPO instrument several weeks leading to the SALT observations were also analysed. The results show that UZ For is ∼ −5% circularly and 5% linearly polarized before the eclipse. A burst of linear polarization is seen just after the eclipse reaching ∼10%. After the eclipse, negative circular polarization reaching ∼ −5% is observed. Both linear and circular polarization are consistent with zero after phase 1.1. The MeerKAT radio observations show a faint source which has a peak flux density of 30.7 ± 5.4 µJy/beam at 1.28 GHz (L-band) at the position of UZ For. This marks the first detection of UZ For at L-band. This study demonstrates that multi-wavelength observations are essential to understanding the various emission processes that are at work in mCVs. The results presented in this thesis shows that UZ For is one of the most interesting AM Her systems known to date. The circular spectropolarimetry results are consistent with those from literature and shows that the SALT telescope will be able to observe other systems like this for detailed analysis. Furthermore, the eclipse times of this system is consistent with the presence of two planets and makes UZ For the second AM Her system after HU Aqr shown to harbour planets and in which additional observations still support earlier conclusions. The radio detection of this system with MeerKAT opens a window to studying other low flux density AM Her systems at L-band radio frequencies in the southern sky.